IDENTIFICATION AND ANALYSIS OF CONSTRAINTS LINKED TO THE INTRODUCTION OF OILSEED CROPS IN ALGERIA. THE CASE OF RAPESEED IN THE WILAYA OF SKIKDA - Ammar, Foufou; Assia, Kalaras; Amira, Farroudj; Fatima Zohra, Dabi; Trifa, Mohamed (The journal of contemporary issues in business and government, 2024)
The aim of this study is to examine the to introduce rapeseed as an oilseed crop in Algeria, using the Wilaya of Skikda, in north-eastern Algeria, as a geographical focus and identifying the constraints facing this crop as a priority objective. This work is spread over two consecutive agricultural seasons (2021 and 2022), during which we carried out field surveys with farmers and professional and technical support organisations, mainly responsible for guidance and extension. These surveys enabled us to build a database which we analysed and dissected to highlight the current situation of this project, its progress and the stages of its implementation with the participation of all the stakeholders concerned and involved. In this respect, 31 farmers were questioned using questionnaires drawn up for this purpose, targeting those in 2021 and those in 2022 so as to be able to monitor and evaluate this project of great economic importance for Algeria, which wants to reduce at all costs the imports of oilseeds that cost the state a lot of money. Our findings revealed that this highly promising project contains a number of shortcomings and imperfections hampering its success and its implementation in time and space. These are technical and agronomic constraints, as well as institutional and administrative ones, which have meant that projects to introduce rapeseed cultivation in the Wilaya of Skikda are now under threat of abandonment by the farmers and investors who rushed to sign up to the project. Our investigations have shown that the project was carried out in haste, without a prior study being carried out and without the human and material resources being made available to the farmers to bring this project to a successful conclusion, which is now sinking into confusion.